THE ROLE OF WORKING CAPITAL TO INCREASE SMALL BUSINESS ENTERPRISES - Fatmawati, Nurul; Nurlaila, Siti Hajar; Sukoco, Agus; Ade, Reswanda T.; Utomo, Wahyu Mulyo (AIBPM Publisher, 2018)
The objective of the research is to find the role of working capital that is sourced from own capital and credit capital in order to increase the value and capacity of small business sector. The research was conducted by surveys, interviews, and documentation of Financial Statement records. The data used in this study is the primary data,based on the analysis of the business credit process. The loan application stage, the review stage, credit analysis,credit approval, credit agreement stage and credit disbursement stage. The results found that the progress of SMEs is determined by the availability of working capital divided on their own capital and loan credit capital. Own capital and capital credit provide a positive and significant impact on business volume on SMEs in Surabaya.